Fabrication of the composite nanofibers of NiO/γ-Al2O3 for potential application in photocatalysis. Issue 15 (15th November 2016) - Li, Biyun; Yuan, Huihua; Yang, Pengfei; Yi, Bingcheng; Zhang, Yanzhong
Abstract: Composite nanofibers of NiO/γ-Al2 O3 were fabricated by sol–gel processing and electrospinning followed by calcination of precursor composite fibers of nickel acetate/aluminum acetate/polyvinylpyrrolidone. Calcination at high temperatures allows for preservation of the NiO/γ-Al2 O3 in fibrous form with a fineness of 322±69 nm in diameter. The composite fibers calcined at 800 or 1000 °C exhibited the nickel oxide and the γ-alumina phases, and higher calcination temperature was found to be in favor of crystalline development. EDS analysis confirmed that the Ni: Al ratio is about the same as the precursor formulation prepared for electrospinning. Finally, photocatalytic activity of the NiO/γ-Al2 O3 nanofibers in comparison with TiO2 nanoparticles was investigated by evaluating the photodegradation of hazardous dye Rhodamine B. It was found that the as-fabricated NiO/γ-Al2 O3 composite nanofibers possessed a photocatalytic efficiency of 85.56%, which was nearly the same photocatalytic activity as the TiO2 nanoparticles but can be recycled more easily. This work offers a direct insight into the comparison of photocatalysis of NiO/γ-Al2 O3 nanofibers and TiO2 nanoparticles and suggests the great potential of using the developed nanofibrous NiO/γ-Al2 O3 for practical photocatalysis applications in various air/water pollution controls.